Inhibition by rebamipide of cytokine-induced or lipopolysaccharide-induced chemokine synthesis in human corneal fibroblasts. Issue 12 (19th August 2014) - Fukuda, Ken; Ishida, Waka; Tanaka, Hiroshi; Harada, Yosuke; Fukushima, Atsuki
Abstract : Background/aims: The dry-eye drug rebamipide has mucin secretagogue activity in and anti-inflammatory effects on corneal epithelial cells. Corneal stromal fibroblasts (transdifferentiated keratocytes) function as immune modulators in the pathogenesis of chronic ocular allergic inflammation and in innate immune responses at the ocular surface. The possible anti-inflammatory effects of rebamipide on human corneal stromal fibroblasts were examined. Methods: Serum-deprived cells were incubated for 1 h with rebamipide and then for various times in the additional absence or presence of cytokines or bacterial lipopolysaccharide (LPS). The release of chemokines into culture supernatants was determined with ELISAs. The intracellular abundance of chemokine mRNAs was quantitated by reverse transcription and real-time PCR analysis. Degradation of the nuclear factor κB (NFκB) inhibitor IκBα was detected by immunoblot analysis. Results: Rebamipide suppressed the release of interleukin (IL)-8 and the upregulation of IL-8 mRNA induced by tumour necrosis factor α (TNF-α) or LPS in corneal fibroblasts. It also inhibited eotaxin-1 (CCL-11) expression at the protein and mRNA levels induced by the combination of TNF-α and IL-4. In addition, rebamipide attenuated the degradation of IκBα induced by TNF-α or LPS. Conclusions: Rebamipide inhibited the synthesis of chemokines by corneal fibroblasts in association with suppression of NFκB signalling. Rebamipide may therefore prove effective for the treatment of corneal stromal inflammation associated with allergy or bacterial infection.